Location of insects in a barley bulk-grain - G. A. Zakladnoy (Зерновое хозяйство России)
In order to reduce the loss of stored grain, it is important to detect insects in it at the early stages of infection, for which it is important to know their preferred habitats. The purpose of the current study was to gain knowledge about the distribution of insects in the top layer of grain, from which samples are taken at enterprises to estimate pest infestation. In the samples taken in five repetitions from a barley bulk-grain stored in a granary, there were identified and counted pest species and their number. The temperature was determined at the sampling sites. The air temperature above the bulk-grain was from minus 2 °С to 0 °С. In layers with a depth of 0–28 cm, 28–56 cm, and 56–84 cm at a mean temperature of 9, 14 and 18°C, respectively, the confidence limits at p = 0.05 were within 5–13, 8–20 and 12–24 °C, respectively. The confidence limits of all three means have overlapped, proving that the difference in mean temperatures is not statistically significant. There have been found three species of insects in grain samples. Beetles Sitophilus oryzae clustered in greater numbers in grain layers where the temperature was higher. Rhizopertha dominica was found only in the warmest bottom layer of the grain. Liposcelis bostrychophila was concentrated in the greatest amount in the second deepest grain layer. There has been found an increase in the crowding of adults of all three species in grain layers with a higher temperature.